STUDIES ON THE ICE STORAGE CHARACTERISTICS OF BLOOD CLAM ANADARA GRANOSA MEAT - BASU, SUBRATA BASU; GUPTA, S S (Fishery Technology, 2017)
Ice-storage study of blood clam ( Anadara granosa) meat in direct contact and out of contact (in 200 gauge polyethylene bag) with ice was taken up to assess the amenability of the meat to icing. Changes in moisture, total protein, non-protein nitrogen, oc amino nitrogen, total volatile base nitrogen, glycogen, free fatty acid, peroxide value, total bacterial count and coliform count were followed every day. The raw and cooked meat were also subjected to organoleptic evaluation. The study showed that the clam meat can be ice-stored in very good condition out of contact with ice in polyethylene packets for 4 days and in direct contact with ice for 2 days